Open laminectomy vs. minimally invasive laminectomy for lumbar spinal stenosis: a review - Utpal K. Dhar; Emma Lilly Menzer; Maohua Lin; Timothy O’Connor; Nischal Ghimire; Elias Dakwar; Ioannis D. Papanastassiou; Kamran Aghayev; Chi-Tay Tsai; Frank D. Vrionis (Frontiers in Surgery, 2024)
ObjectivesLumbar spinal stenosis (LSS) refers to a narrowing of the space within the spinal canal, which can occur at any level but is most common in the lumbar spine. Open laminectomy and minimally invasive laminectomy (MIL) procedures are the most common surgical gold standard techniques for treating LSS. This study aims to review clinical and biomechanical literature to draw comparisons between open laminectomy and various MIL techniques. The MIL variation comprises microendoscopic decompression laminotomy, unilateral partial hemilaminectomy, and microendoscopic laminectomy.MethodsA review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We reviewed 25 clinical, 6 finite element, and 3 cadaveric studies associated with treating LSS. We reviewed literature that discusses factors such as operation time, length of hospital stay, postoperative complications, reoperation rate, effect on elderly patients, patients’ satisfaction, and adjacent segment disease degeneration for the clinical studies, whereas the range of motion (ROM), von Mises stresses, and stability was compared in biomechanical studies.ResultsMIL involves less bone and ligament removal, resulting in shorter hospital stays and lower reoperation and complication rates than open laminectomy. It improves the quality of health-related living standards and reduces postoperative pain. Biomechanical studies suggest that laminectomy and facetectomy increase annulus stress and ROM, leading to segmental instability.ConclusionAlthough theoretically, MIL means less tissue injury, pain, and faster recovery in the short term, the long-term results depend on the adequacy of the decompression procedure and tend to be independent of MIL or open laminectomy.